Interest in treatment with injectable diacetylmorphine among people who use opioids in Baltimore City, Maryland (USA). (12th December 2023) - Allen, Sean T.; Schneider, Kristin E.; Rouhani, Saba; White, Rebecca Hamilton; Morris, Miles; Owczarzak, Jill; Sherman, Susan G.
Abstract: Introduction: Treatment for opioid use disorder (OUD) with diacetylmorphine is an evidence-based form of drug treatment, but it is not available in the United States (US). Better understanding acceptability of treatment with injectable diacetylmorphine among people who use opioids (PWUO) in the US may expedite future initiatives designed to engage persons in this form of treatment should it become available. The purpose of this research is to examine factors associated with interest in treatment with injectable diacetylmorphine among a sample of PWUO in the US. Methods: Data are from a cross-sectional study of PWUO in Baltimore City, Maryland. Participants were given a brief description of treatment with injectable diacetylmorphine and then asked to rate their level of interest. We used Poisson regression with robust variance to assess factors associated with interest in treatment with injectable diacetylmorphine. Results: The average age of participants was 48 years, 41% were women, and most (76%) identified as non-Hispanic, Black. The most commonly used substances were non-injection heroin (76%), opioid pain relievers (73%), and non-injection crack/cocaine (73%). Two-thirds of participants (68%) indicated interest in treatment with injectable diacetylmorphine. Factors significantly associated with interest in injectable diacetylmorphine treatment included: having at least a high school education (adjusted prevalence ratio [aPR]: 1.23; 95% confidence interval [CI]: 1.04–1.45), not having health insurance (aPR: 1.23; 95% CI: 1.06–1.44), having ever overdosed (aPR: 1.20; 95% CI: 1.01–1.42), and past utilization of medications for opioid use disorder (aPR: 1.22; 95% CI: 1.01–1.47). Recent non-injection cocaine use was inversely associated with interest in treatment with injectable diacetylmorphine (aPR 0.80; 95% CI: 0.68–0.94). Conclusion: The majority of participants reported interest in treatment with injectable diacetylmorphine. Given worsening trends in the addiction and overdose crisis in the US, treatment with injectable diacetylmorphine should be considered as another evidence-based option for treating OUD. KEY MESSAGES: Interest in treatment with injectable diacetylmorphine was high among a sample of people who use opioids in the United States. Factors associated with increased interest in treatment with injectable diacetylmorphine included having at least a high school education, having ever overdosed, and not having health insurance. Past utilization of medications for opioid use disorder was associated with interest in treatment with injectable diacetylmorphine.